Management of cutaneous squamous cell carcinoma in patients with epidermolysis bullosa: best clinical practice guidelines. (7th November 2015) - Mellerio, J.E.; Robertson, S.J.; Bernardis, C.; Diem, A.; Fine, J.D.; George, R.; Goldberg, D.; Halmos, G.B.; Harries, M.; Jonkman, M.F.; Lucky, A.; Martinez, A.E.; et al.
Summary: This article summarizes recommendations reached following a systematic literature review and expert consensus on the diagnosis and management of cutaneous squamous cell carcinomas in people with epidermolysis bullosa. The guidelines are intended to help inform decision making by clinicians dealing with this complex complication of a devastating disease. Abstract : What's already known about this topic? Some subtypes of epidermolysis bullosa (EB), particularly severe generalized recessive dystrophic EB, are associated with the development of mucocutaneous squamous cell carcinomas (SCCs). These tumours behave aggressively and are a leading cause of morbidity and mortality in at‐risk patients with EB. What does this study add? These guidelines will assist clinicians in the diagnosis, management and staging of EB‐associated cutaneous SCCs based on available evidence and expert consensus. They highlight the importance of a holistic multidisciplinary approach to the management of EB‐associated SCCs, where patient involvement in decision making is paramount. Linked Comment: Krupiczojc and O'Toole. Br J Dermatol 2016 ; 174: 15 .